2006
DOI: 10.1016/j.cemconres.2004.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Autogenous deformations of cement pastes

Abstract: A micro-macro experimental study has been performed, from the end of mixing up to 2 years, on a set of plain cement pastes prepared with the same type I ordinary Portland cement (OPC) and various water-to-cement ratios (W/C), and cured at various constant temperatures. In this part I of the paper, volumetric autogenous shrinkage has been analysed in relation to various parameters characterizing the hydration process: chemical shrinkage, degree of hydration of the cement, Ca(OH) 2 content and Vicat setting time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(36 citation statements)
references
References 23 publications
2
23
1
1
Order By: Relevance
“…The best way to suppress moisture gradients and the related size effect is to proceed by sealing samples. This has been done by BaroghelBouny and Kheirbek [8], on sealed cylinders of hardened cement paste, and for a large range of the water-cement ratio. It was very difficult for them to find a test procedure for tree sealed conditions that completely suppressed any mass exchange with the ambient medium.…”
Section: Swelling or Shrinkage : What Is Specific To Cement Hydration?mentioning
confidence: 99%
“…The best way to suppress moisture gradients and the related size effect is to proceed by sealing samples. This has been done by BaroghelBouny and Kheirbek [8], on sealed cylinders of hardened cement paste, and for a large range of the water-cement ratio. It was very difficult for them to find a test procedure for tree sealed conditions that completely suppressed any mass exchange with the ambient medium.…”
Section: Swelling or Shrinkage : What Is Specific To Cement Hydration?mentioning
confidence: 99%
“…Moreover, for comparison, the autogenous shrinkage strains, provided by Lee et al [60] and by Baroghel-Bouny et al [63] for similar concrete mixtures, are shown. Whereas the water to cement ratio as well as the aggregate to cement ratio of the concrete mixtures investigated in the studies [60], [63] and in the present study are quite similar, the maximum aggregate size of the respective concrete mixtures is quite different, ranging from 19 and 20 mm for the mixtures described in the studies [60,63] to 32 mm (Table 1) for the one investigated in the present study. The size and shape of the specimens used in Lee et al [60] and in Baroghel-Bouny et al [63] and in the present study are different.…”
Section: Resultsmentioning
confidence: 93%
“…The measured total shrinkage includes both drying and autogenous shrinkage (thermal deformation can be ignored due to the small cross-section of the samples (Baroghel-Bouny et al, 2006)). For very low w/c, the contribution of autogenous shrinkage to the total shrinkage can be comparable to that of drying shrinkage (Soliman, 2011).…”
Section: Shrinkagementioning
confidence: 99%